PEMBELAJARAN MUSIKALISASI PUISI MELALUI MODEL PENGAJARAN LANGSUNG - Sukarti (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2016)
Poetry-making skill as well as providing appropriate tune that matches the atmosphere of the poetry or musical poetry skills is not an easy task. In pursuit of learning, especially learning musical poetry, teachers demanded to be able to use appropriate teaching methods. Learning musical poetry is strongly influenced by the skills, knowledge, experience and creativity of each teacher. Because learning musical poetry appreciation is given with all the limitations of teachers, which is considered to make the results of musical poetry achieved isnot maximum. Through direct instruction is expected to increase the motivation and skills of students in musical poetry. Each stage of learning in direct teaching methods give students the opportunity to take part starting from the selection of poetry, determining the atmosphere of poetry, poetry atmosphere synchronization with music, training, performance, and evaluation. With direct instruction, students will be motivated to perform activities of musical poetry with pleasure. They can be taken deep into learning without any psychological pressure, but instead feeling the excitement.